Numerical Modelling of Droplet Breakup for Flash-Boiling Fuel Spray Predictions - Price,C; Hamzehloo,A; Aleiferis,P; Richardson,D (International Journal of Multiphase Flow, 2020)
Flash-boiling of fuel sprays can occur under injection of superheated fuel into ambient pressure that is lower than the saturation pressure of the fuel and can dramatically alter spray formation due to complex two-phase flow effects and rapid droplet evaporation phenomena. Such phenomena exist in-cylinder at low-load in-city driving conditions where strict engine emission regulations apply, hence the need for faithful flash-boiling fuel spray models by engine designers. To enhance the current modelling capability of superheated fuel sprays, with focus on near-nozzle plume expansion, a flash-boiling breakup modelling approach was developed to introduce the thermal breakup mechanism of droplets caused by nucleation and bubble growth. This model was particularly aimed at sprays where levels of superheat introduced noticeable radial expansion of the plumes upon discharge from the nozzle orifice. The model was able to simulate droplet shattering by introducing Lagrangian child parcels at breakup sites with additional radial velocity components instigated by rapid bubble growth and surface instabilities. Combination of the flash-boiling droplet breakup model with a flash-boiling effective nozzle model that was used as boundary condition for the spray plumes offered a more complete modelling approach, where both in-nozzle phase change effects and near-nozzle flashing through droplet shattering were incorporated into the Eulerian-Lagrangian two-phase computational framework. Sensitivity studies were carried out to investigate important parameters which are inherently difficult to measure experimentally and offered valuable insight into modelling superheated sprays. The model was able to capture important flash-boiling spray characteristics and quantitative validation was achieved through comparison to experimental data in the form of penetration lengths and droplet sizes with a good level of agreement.